Fabrication of bacterial cellulose, chitosan and essential oil biocomposite for antimicrobial effect - Noor Faridatul Akhamar, Simbun (2010)

(untitled)
Chronic wounds represent a significant burden to patients, health care professionals and the health care system. Therefore healing process is very important to avoid inflammation to the wound area. The objectives of this study were to produce biocomposite film from bacterial cellulose, chitosan and essential oil and study the characterization of the biocomposite film by using Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscope (SEM), pycnometer, antimicrobial effect, biodegradability testing and water absorption. The film was synthesized by using mixing and casting process and bacterial cellulose is produced by Acetobactor Xylinum. The samples contain three different amount of chitosan which were (25%, 50%, 75%). The FTIR showed the interaction between components at 3000-3500 cm which is OH bonding besides that it also show the, C=O at band 1651 cm -1 and also amine group at 1550-1580 cm-1. From the antimicrobial test, the sample contain of 75% chitosan showed the higher percentage of effectiveness to kill the bacteria and good water absorption. Then from the density testing, the result showed the sample was contain 75% chitosan have high density and have lower degradable rate. Moreover the SEM analysis these film showed smooth, compactable and homogenous structure. In conclusion, the objectives in this study were achieved and the biocomposite film contain bacterial cellulose, chitosan and essential oil had a potential in medical application especially for wound healing.